(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2021)
In the present essay, I will take into account some Italian war films made in the 1950s, such as “Carica eroica” (“Heroic Charge”, 1952, Francesco De Robertis), “I sette dell’Orsa maggiore” (“Hell Raiders of the Deep”, 1953, Duilio Coletti), “Mizar - Sabotaggio in mare” (Mizar, 1954, Francesco De Robertis), “Divisione Folgore” (“Folgore Division“, 1954, Duilio Coletti), “La grande speranza” (“Submarine Attack”, 1954, Duilio Coletti) in order to reflect upon their role in building Italy’s memory of its past as well as the perception of Italian war crimes in public opinion. These productions extend a unifying narrative of the war, consolidating the myth of the “good Italian” (“italiani brava gente”). Through the inclusion of the soldier in collective memory by silencing his role as aggressor, Italian combat films participated and consolidated the process of collective amnesia about the fascist regime and how they influenced the way in which Italian viewers constructed a shared sense of the past.